HUKUM MENYUCIKAN NAJIS DENGAN SELAIN AIR (STUDI KOMPARASI PANDANGAN MAZHAB HANAFĪ DAN MAZHAB SYAFI’I) - Ariesman M; Abdul Munawir; Muhammad Feril Ramsi (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2025)
This study aims to examine and understand the perspectives of Islamic scholars, particularly those of the Hanafi and Shafi’i schools of thought, regarding the purification of impurities using substances other than water. The research focuses on three main aspects: first, the Hanafi school's perspective on purifying impurities without water; second, the Shafi’i school's perspective on the same issue; and third, a comparative analysis of the differences between these two schools on this matter. This study employs a qualitative descriptive approach using library research methods and adopts both normative and comparative approaches. The findings indicate that, first, according to the Hanafi school, purification is not strictly limited to water but can also be achieved through other means, as exemplified in the practice of istijmar (purification with stones). The Hanafi scholars argue that as long as the impurity’s color, odor, and taste are completely removed, its legal status as an impurity is also nullified. Second, the Shafi’i school mandates the use of water for purification, based on the belief that Allah has bestowed water as a means of purification. Imam Shafi’i asserts that water possesses a unique legal capacity to remove impurities. Third, the fundamental difference between these two schools lies in the necessity of water, where the Hanafi school permits alternative substances, while the Shafi’i school strictly requires water, citing prophetic traditions that exclusively mention purification with water.